Expressing the Essence of Classical Gambuh Dance Drama through Batuan Traditional Painting - Barde, Ashlesha; Purnami Utami, Ni Made; Bendi Yudha, I Made (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2026)
This independent study project explores how the essence of Gambuh, Bali’s oldest and most sacred dance-drama, can be interpreted through the lens of traditional Batuan painting. Motivated by a desire to preserve and reinterpret cultural heritage, this project focuses on visualizing six main characters, Putri Rangkesari, Panji, Condong, Prabhu Lasem, Kade-Kadean, and Arya, each rendered with deep attention to gesture, costume, and symbolic presence. The research employs a method rooted in artistic creation, combining aesthetic approaches such as heuristic, hermeneutic, and symbolic exploration with field observations and traditional mentorship. The creative process followed three key stages: exploration through direct observation of Gambuh performances and Batuan traditional painting studios; improvisation through sketching and experimenting with visual composition; and forming, where the final works were developed using Chinese ink and watercolor on watercolor paper and canvas in the Batuan style. The artworks produced do not merely document the characters but reinterpret them as reflections of emotional and philosophical dimensions relevant to today’s social reality. This project concludes that Batuan painting offers a powerful visual medium to convey the layered narratives of Gambuh, enabling the audience to engage with classical themes of love, power, longing, and moral conflict through a contemplative visual experience.